Cognitive Flexibility in Young Children: Beyond Perseveration. (9th August 2016) - Carroll, Daniel J.; Blakey, Emma; FitzGibbon, Lily
Abstract: Cognitive flexibility (CF) is the ability to rapidly adjust our thoughts and behaviors in response to changes around us. Although studies of preschoolers have contributed to our understanding of how this ability emerges, progress has slowed in recent years because of methodological and conceptual issues. In this article, we outline recent developments that address these issues and that have led to a more nuanced understanding of CF—particularly regarding the role of perseveration. We propose that CF is a diverse and multifaceted skill that involves more than just overcoming perseverative errors.